2009
DOI: 10.1089/jmf.2007.0568
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Fresh and Processed Fruit Bodies and Mycelium of Auricularia auricula-judae (Fr.) Quél

Abstract: Auricularia auricula-judae is currently grown in Malaysia. In the present study, the methanolic extracts from fruit bodies (fresh, oven-dried, and freeze-dried) and mycelium of A. auricula-judae were evaluated for their antioxidant capacities based on 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and ferric reducing antioxidant power (FRAP) assay. The total phenolic content in the extracts were also measured. The extract of freeze-dried fruit bodies of A. auricula-judae had potent DPPH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…The radical scavenging activity of a sample can be measured as a decolorizing effect following the trapping of the unpaired electron of DPPH. 9 There was no difference in soluble antioxidant content between black and white mushrooms (Fig. 2F, G).…”
Section: Analyses Of Melanin and Antioxidant Contents In Black And Whmentioning
confidence: 85%
See 1 more Smart Citation
“…The radical scavenging activity of a sample can be measured as a decolorizing effect following the trapping of the unpaired electron of DPPH. 9 There was no difference in soluble antioxidant content between black and white mushrooms (Fig. 2F, G).…”
Section: Analyses Of Melanin and Antioxidant Contents In Black And Whmentioning
confidence: 85%
“…7 The antioxidant capacity of methanol extracts from black and white mushrooms in 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was measured as in. 9 In vivo fluorescent imaging All animal studies were carried out in accordance with the guidelines of the Animal Care and Use Committee. Six-to eight-week-old CD-1 female mice (Charles River Breeding Laboratories, Portage, MI) were used in all experiments.…”
Section: Melanin Sources and Physicochemical Analysesmentioning
confidence: 99%
“…Due to the inconsistency of many radical system used for antioxidant evaluation, it is widely suggested that at least two different methods should be applied to investigate the radical-scavenging capacities of selected antioxidant or a food system [16]. Because of the importance of antioxidant capacity in the prevention of atherosclerosis, the hydroxyl and superoxide anion radical systems were adopted to investigate the antioxidant effects of AHP functional diet.…”
Section: Radical-scavenging Effects In Vitromentioning
confidence: 99%
“…In recent years, A. auricula-judae has been reported to have the functions of lowering blood cholesterol and triglycerides (Chen et al 2008), preventing strokes and heart attacks , and effective in treating diabetes ) and certain cancers (Ma et al 2010). It also exhibits antioxidant activities (Kho et al 2009). Therefore, A. auricula-judae enjoys popular favor in Europe, America, Japan, Korea, Malaysia, Indonesia and Thailand.…”
Section: Introductionmentioning
confidence: 99%